Ruski starci in starčevstvo - Arko, Alenka (Edinost in dialog, 2023)
The paper outlines the historical background of the phenomena of starets (starchestvo) in monasticism, which has its roots in the early days of monastic life in Egypt and is primarily linked to the education of young monks under the guide of an experienced teacher. Particular attention is paid to the development of the phenomena in Russia, which, although with a time lag, initially imitated the Byzantine tradition, but nevertheless in the 18th and 19th centuries developed original traits, especially around the monastery of Optina Pustyn and the figure of the starets Macarius, who opened the monasticism »outwards« and became a spiritual guide of the laity – the intelligentsia and the common people. The monastery's connection with the world later led to specific forms of elderhood in which also diocesan priests and even lay people, men and women, were recognised as starets. Of course, this was largely connected with the historical situation in Russia, with the communist persecution of monks and the closure of monasteries. Particularly outstanding are the so-called »yurodiviy« (fools for Christ), who are an unique embodiment of God's wisdom and its redemptive power. The paper attempts to present the basic traits of the spirituality of the starets and the relationship with his spiritual sons and daughters from the perspective of Russian scholars. We can see a deeply Trinitarian and Christologically rooted spirituality, which presupposes a kenotic attitude of the starets in order that the person who is led by him reach God through him. Far from any spiritual manipulation and domination, the unique aim of the starets is to lead the spiritual son or daughter to theosis, divinisation, i.e., to freely accept the grace of salvation.
Keywords: duhovno vodstvo; duhovno življenje; hesihazem; hesychasm; jurodivji; meništvo; monastery in the world; monasticism; ruski starci; Russian starets; samostan v svetu; spiritual accompaniment; spiritual life; yurodiviy (fool for Christ)